Suplementação de nucleotídeos na dieta de alevinos de tilápia do Nilo (Oreochromis niloticus) : desempenho zootécnico, histomorfometria intestinal e respostas fisiológicas - Delgado, Maria Karolaine Moriman (2022)
Functional aquatic nutrients such as nucleotides have been studied for the beneficial effects they can provide on animal growth, intestinal maturation and modulation of the immune system. Therefore, the objective of this study was to evaluate the zootechnical performance, biometric indices, intestinal histomorphometry, biochemical parameters indicating stress and innate immunity of Nile tilapia fingerlings supplemented with nucleotides in the diet and subjected to vaccination management. The animals were distributed in a completely randomized experimental design, consisting of two treatments and six replications. The treatments consisted of two levels of inclusion of a commercial mixture of nucleotides in proportions of 0.0 and 2.0 g kg¹ of feed. For the present study, 12 experimental units were used arranged in a closed water recirculation system with constant aeration. The fish were subjected to vaccination management and blood sampling at different sampling times (before vaccination, 3 and 7 days after vaccination) to investigate biochemical parameters indicating stress and innate immunity. The results of the study were compared using analysis of variance and, when significant (p<0.05), they were subjected to the Student's t and Tukey tests. Dietary nucleotide supplementation reduced the standard length and height of fish and increased the intestinal coefficient. Zootechnical performance and other intestinal histomorphometric parameters were not changed. The inclusion of NT in the diet did not affect the biochemical parameters indicating stress, however it provided lower values ​​of total protein and globulin and decreased the respiratory activity of leukocytes before and three days after vaccination.